2008
DOI: 10.1210/en.2008-0015
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress-Induced Activation of Activating Transcription Factor 6 Decreases Insulin Gene Expression via Up-Regulation of Orphan Nuclear Receptor Small Heterodimer Partner

Abstract: The highly developed endoplasmic reticulum (ER) structure of pancreatic beta-cells is a key factor in beta-cell function. Here we examined whether ER stress-induced activation of activating transcription factor (ATF)-6 impairs insulin gene expression via up-regulation of the orphan nuclear receptor small heterodimer partner (SHP; NR0B2), which has been shown to play a role in beta-cell dysfunction. We examined whether ER stress decreases insulin gene expression, and this process is mediated by ATF6. A small in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
91
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 36 publications
14
91
0
4
Order By: Relevance
“…Accumulating evidence suggests that a cross-talk exists between the ATF6α and IRE1α-XBP1s pathways to achieve maximal induction of their downstream target genes [5,6,48]. A recent study revealed deleterious effects of ATF6α overexpression on beta cell function and expression of insulin, PDX1 and MAFA in INS-1 cells [49]. Together with our data in primary cells, this suggests that the ATF6α and XBP1 pathways may have redundant roles in the regulation of insulin expression and secretion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Accumulating evidence suggests that a cross-talk exists between the ATF6α and IRE1α-XBP1s pathways to achieve maximal induction of their downstream target genes [5,6,48]. A recent study revealed deleterious effects of ATF6α overexpression on beta cell function and expression of insulin, PDX1 and MAFA in INS-1 cells [49]. Together with our data in primary cells, this suggests that the ATF6α and XBP1 pathways may have redundant roles in the regulation of insulin expression and secretion.…”
Section: Discussionsupporting
confidence: 82%
“…However, due to the deleterious effects of prolonged increased XBP1s level, this mechanism has to be closely regulated in beta cells, resulting in a limited XPB1 splicing as shown by previous studies [2,12] and the present data. These observations, together with other studies showing detrimental effects of prolonged eukaryotic translation initiation factor 2 alpha (eIF2α) or ATF6α activation in beta cells [24,49], suggest that tight control of ER homeostasis is crucial to maintain beta cell function and survival.…”
Section: Discussionmentioning
confidence: 80%
“…Under ER stress, ATF6 is activated, leading to a decrease in insulin gene expression. 34 This suggests that ATF6 may have dual functions: positive regulation of chaperones and negative regulation of insulin promoter activity. The involvement of the UPR triad (i.e., IRE1, PERK and ATF6) in b-cell proteostasis and insulin biosynthesis illustrates translation of UPR target mRNAs, such as activating transcription factor 4 (ATF4).…”
Section: The Er Stress Signaling Triadmentioning
confidence: 99%
“…Contrary to the opinion that the ATF6 family contributes to alleviating cellular stress [9,16,24] , the studies by Seo et al suggest that ATF6 plays an important role in the development of β-cell dysfunction [49] . Although ATF6 was shown to suppress insulin gene expression in INS-1 cells, this process might be a feedback to prevent hyperinsulinmia in vivo.…”
Section: Discussionmentioning
confidence: 84%